2015
DOI: 10.1016/j.micres.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis of salt acclimated Prochlorococcus AS9601

Abstract: Molecular processes leading to salt stress acclimation in the model cyanobacterium Prochlorococcus are not known. To address this, we used RNA sequencing (RNAseq) to compare the global transcriptome of two exponential-phase populations of Prochlorococcus AS9601 cells - acclimated to high salt (5%, w/v) and normal seawater salt (3.8%, w/v). Experiments showed that salt acclimated cells exhibit slower growth rates with a doubling time almost twice as controls. Approximately 1/3 of the genome was found to be diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Chaperones, molecules with an important role in protein folding, protection, and repair under stress conditions, were highly up-regulated in our study. Their role in maintaining protein integrity under low and high salt stress was previously described (Fulda et al, 2006 ; Al-Hosani et al, 2015 ). The cell wall is the first part encountering a new environment, and thus cell wall structure and functioning have a crucial role in adaptation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Chaperones, molecules with an important role in protein folding, protection, and repair under stress conditions, were highly up-regulated in our study. Their role in maintaining protein integrity under low and high salt stress was previously described (Fulda et al, 2006 ; Al-Hosani et al, 2015 ). The cell wall is the first part encountering a new environment, and thus cell wall structure and functioning have a crucial role in adaptation.…”
Section: Discussionmentioning
confidence: 98%
“…Genomes of cyanobacteria are highly dynamic and the induction of either general or stress-specific genes and regulatory systems enable them to proliferate in a changing environment. Transcriptome modifications that acclimate to elevated salt concentration are induced rapidly (Billis et al, 2014 ), but complete acclimation of metabolic processes resulting in the inhibition of cell division requires a longer time period (Qiao et al, 2013 ; Al-Hosani et al, 2015 ). For example, work on Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of either general or stress-specific genes and regulatory systems enables cyanobacteria to thrive, even in changing environments. The transcriptional regulatory system of model cyanobacteria for adapting to elevated salt concentrations is induced rapidly 31 , but complete acclimation of metabolic processes resulting in inhibition of cell division requires longer periods of time 33,34 . For example, a study of Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The pentose phosphate pathway belongs to the carbon fixation pathway in S. elongatus. It was reported that the transcript abundance of carbon fixation was increased in Prochlorococcus AS9601 under salt stress (Al-Hosani et al, 2015). The results suggested that Syn2973 elevated pentose phosphate pathway, which might fix more carbon dioxide for salt tolerance, and overexpressing 7002-Mrp has no inference on the mechanism.…”
Section: Comparative Targeted Metabolomics Analysis Of Strains Jy13 and Jy00mentioning
confidence: 93%